Isolation and Molecular Profiling of Primary Mouse Retinal Ganglion Cells: Comparison of Phenotypes from Healthy and Glaucomatous Retinas - Chintalapudi, Sumana R.; Djenderedjian, Levon; Stiemke, Andrew B.; Steinle, Jena J.; Jablonski, Monica M.; Morales-Tirado, Vanessa M. (Frontiers in Aging Neuroscience, 2016)
Loss of functional retinal ganglion cells (RGC) is an element of retinal degeneration that is poorly understood. This is in part due to the lack of a reliable and validated protocol for the isolation of primary RGCs. Here, we optimize a feasible, reproducible, standardized flow cytometry-based protocol for the isolation and enrichment of homogeneous RGC with the Thy1.2hiCD48negCD15negCD57neg surface phenotype. A three-step validation process was performed by (1) genomic profiling of 25-genes associated with retinal cells, (2) intracellular labeling of homogeneous sorted cells for the intracellular RGC-markers SNCG, BRN3A, TUJ1, and RBPMS; and (3) by applying the methodology on RGC from a mouse model with elevated IOP and optic nerve damage. Use of primary RGC cultures will allow for future careful assessment of important cell specific pathways in RGC.